Immunomodulatory Properties of DNA Hypomethylating Agents: Selecting the Optimal Epigenetic Partner for Cancer Immunotherapy - Fazio, Carolina; Covre, Alessia; Cutaia, Ornella; Lofiego, Maria Fortunata; Tunici, Patrizia; Chiarucci, Carla; Cannito, Sara; Giacobini, Gianluca; Lowder, James N.; Ferraldeschi, Roberta; Taverna, Pietro; Di Giacomo, Anna Maria; et al. (Frontiers in Pharmacology, 2018)
DNA hypomethylating agents (DHAs) play a well-acknowledged role in potentiating the immunogenicity and the immune recognition of neoplastic cells. This immunomodulatory activity of DHAs is linked to their ability to induce or to up-regulate on neoplastic cells the expression of a variety of immune molecules that play a crucial role in host-tumor immune interactions. To further investigate the clinical potential of diverse epigenetic compounds when combined with immunotherapeutic strategies, we have now compared the tumor immunomodulatory properties of the first generation DHAs, azacytidine (AZA) and decitabine (DAC) and of the next generation DHA, guadecitabine. To this end, human melanoma and hematological cancer cells were treated in vitro with 1 μM guadecitabine, DAC or AZA and then studied by molecular and flow cytometry analyses for changes in their baseline expression of selected immune molecules involved in different mechanism(s) of immune recognition. Results demonstrated a stronger DNA hypomethylating activity of guadecitabine and DAC, compared to AZA that associated with stronger immunomodulatory activities. Indeed, the mRNA expression of cancer testis antigens, immune-checkpoint blocking molecules, immunostimulatory cytokines, involved in NK and T cell signaling and recruiting, and of genes involved in interferon pathway was higher after guadecitabine and DAC compared to AZA treatment. Moreover, a stronger up-regulation of the constitutive expression of HLA class I antigens and of Intercellular Adhesion Molecule-1 was observed with guadecitabine and DAC compared to AZA. Guadecitabine and DAC seem to represent the optimal combination partners to improve the therapeutic efficacy of immunotherapeutic agents in combination/sequencing clinical studies.